Neuroprotective properties of nigella sativa (L.) seeds extract in sprague dawley rats models - Babar, Zahir Uddin; Azad, Abul Kalam; Wan Sulaiman, Wan Mohd Azizi; Uddin, Jalal; Labu, Zubair Khalid (University of Dhaka, 2018)
Neuroinflammation has been closely linked to neurodegeneration that leads to dysfunction of memory and learning where glial fibrillary acidic protein (GFAP) plays important role positively within hippocampus. In experimental neurodegeneration achieved by two-vessel occlusion (2VO) intervention, Nigella sativa (L.) seeds extract (50 mg/kg/day orally) has shown to have anti-neuroinflammatory and antioxidant properties. The brain hippocampal tissues were humanely collected at the end of 10th treatment week and preserved in Allprotect™ reagent at –80°C. Total RNA was extracted and purified by phenol/chloroform method using kits and reverse transcribed into cDNA and relatively quantified as per ∆∆Cq. The NSSE treatment showed significantly (p<0.001) different relative GFAP mRNA expression in the treated group as compared to that of untreated 2VO whilst it was insignificantly (p>0.5) different to that of healthy control (HC). Prolonged or daily treatment with NSSE (Nigella sativa (L.) seeds extract) may provide moderate anti-neuroprotective activity within hippocampus.